NARUSZENIE NORMY KRAJOWEJ PRZY WYRAŻANIU WOLI ZWIĄZANIA SIĘ TRAKTATEM PODEJŚCIE PRAWNOMIĘDZYNARODOWE - Kałduński, Marcin (Wydział Prawa i Administracji UAM, 2007)
Poland has concluded double taxation treaties with Bangladesh, Jordan and Island. These treaties, however, were ratified without the consent o f Parliament. The question raised in the paper is whether such consent to be bound by the treaties as expressed in the ratification instruments is valid under international law. The author argues that i f the rules of international law are to be followed, the validity of the said treaties cannot be challenged. The author then discusses the state practice, judicial decisions and the doctrine of international law. In order to prove the validity of the double taxation treaties in question, the Vienna Convention on the Law of Treaties, and the provisions included in Article 46 and 45 concerning the invalidity of treaties in particular, are quoted. It is argued that the violation of a provision of national law regarding competence to conclude treaties cannot be invoked and that Poland has lost the right to invoke Article 46 of the VCLT that could constitute the ground for invalidating the treaties concluded with Bangladesh, Island and Jordan without its Parliament’s consent.
VIOLATION OF A PROVISION OF INTERNAL LAW TO EXPRESS CONSENT TO BE BOUND BY A TREATY. THE INTERNATIONAL LAW APPROACH